ATTENTION LEVEL OF STUDENTS CHOOSING SOCIAL SCIENCE TADRIS STUDY PROGRAM AT SAYYID ALI RAHMATULLAH UIN TULUNGAGUNG PERSPECTIVE GENDER - Jani, Jani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The research context includes the opening of general study programs at religious-based universities or under the Ministry of Religion, especially the Social Studies Tadris study program, the open opportunity to pursue general education in the Ministry of Religion universities for all genders (men and women), especially in the Social Studies Tadris study program, and community support in the implementation of the Social Studies Tadris study program. This type of research is in the form of exploratory research that focuses more on finding explanations about the truth of the level of attention of students choosing the Tadris IPS study program from a gender perspective. Data retrieval through 2 techniques. First, through the study of documents in the form of photographs, graphs, sheets, and tables. Second, the data from the interview is in the form of a description from the source's review. The analysis using an interactive model emphasizes data that is directly related to research themes related to the level of attention of students choosing the Social Studies Tradis study program from a gender perspective. The validity of the data in the form of a dependability test, researchers conducted an audit of the initial to final process related to the level of attention of students choosing the Social Studies Tradis study program from a gender perspective. There are 3 researchers' findings. First, equal rights of education of women and men. Every student has the same right in education without any cultural, gender, social, or ethnic distingencies. Second, the escalation of women's attention in the field of social sciences. Every year the attention of women in the field of social sciences has escalated consistently until 2020. In 2021, there was a reduction of 2 students. Then in 2022 it has escalated to reach 4 students. Third, the reduction of male attention in the field of social sciences. The lack of annual attention of men in the field of social sciences. This can be seen through the comparison of the total attention of all women and men in the field of social sciences listed in the table. The purpose of the researcher is to analyze and find the level of attention of students choosing the Tadris IPS study program from a gender perspective. Keywords: Attention, Tadris IPS, Gender.